2019
DOI: 10.1016/j.jacl.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The patient journey with proprotein convertase subtilisin/kexin type 9 inhibitors in community practice

Abstract: BACKGROUND: Trials have demonstrated that proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are effective as an adjunct to statin therapy, but access and cost issues have limited their use in community practice. OBJECTIVE: The aim of the study was to better understand patients' experiences when trying to obtain, fill, and use PCSK9 inhibitor therapy in community practice. METHODS: We conducted a patient survey to evaluate patient experiences with PCSK9 inhibitors including medication initiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Even though one of the most frequently reported adverse reactions in trials was injection site reactions, the subcutaneous administration of PCSK9 inhibitors was well accepted by patients [22]. In addition, multiple studies evaluating PCSK9 inhibitors treatment acceptance suggested a high level of drug acceptance and tolerability [23][24][25]. In the present OLE study, two (0.4%) participants had at least one device-related TEAE, including injection site hematoma in one (0.7%) participant and injection site reaction and application site pruritus in one (0.7%) participant.…”
Section: Discussionmentioning
confidence: 99%
“…Even though one of the most frequently reported adverse reactions in trials was injection site reactions, the subcutaneous administration of PCSK9 inhibitors was well accepted by patients [22]. In addition, multiple studies evaluating PCSK9 inhibitors treatment acceptance suggested a high level of drug acceptance and tolerability [23][24][25]. In the present OLE study, two (0.4%) participants had at least one device-related TEAE, including injection site hematoma in one (0.7%) participant and injection site reaction and application site pruritus in one (0.7%) participant.…”
Section: Discussionmentioning
confidence: 99%
“…Of those who initiated treatment, 34% had discontinued treatment by the time of the survey with half taking the drug for 6 months or less, citing out-of-pocket costs as the leading reason for discontinuation. 24 Other impediments to insurance authorization include insistence on the patient failing ezetimibe on top of a statin in achieving adequate LDL-C reduction, refusing to accept documentation of statin intolerance, the absence of staff with the needed time or expertise to work through the authorization process, as well as the absence of nursing or other staff who can take the needed time to teach patients on the use of PCSK9i.…”
Section: Discussionmentioning
confidence: 99%
“…The date of the first alirocumab or evolocumab claim identified during the selection window was the index date. Given the known access hurdles for PCSK9is, [ 25 ] the cohort was restricted to prevalent patients (those with at least one filled prescription prior to the index date) to minimize the effect of interrupted or discontinued use due to prior authorization hurdles during first treatment initiation, and to isolate the effect due to list price change more effectively (rather than other access hurdles).…”
Section: Methodsmentioning
confidence: 99%